Laryngeal Perforation by Projectile by Firearm - Carrillo, Carol Atzimba Zepeda; García, Baruj Ricardo Lupio; Pazos, Mauricio Israel Flores; Barrón, Gema Méndez; Valiente, Mariana González; Rosas, Areli Stephanie Delia Hernández; Amaro, Dianna Estefany Lopez; Larios, Zuri Sadai Grez; de Oca Ambriz, Iñaki Rubén Montes; Sánchez, Morelos Adolfo García (British Journal of Healthcare and Medical Research, 2024)
Introduction: Neck trauma represents from 5 to 10% of aggressions and with a mortality rate of up to 7%. Laryngeal trauma is fatal, with mortality of up to 80%. Objective: Presentation of a case and review of the literature. Method: A 21-year-old male is in the emergency department with a gunshot wound to the neck. Surgical exploration of the neck was performed, with injury to the larynx at the level of the thyroid cartilage on the anterior and superior aspect with destruction in 30%, 2 x 3 cm multifragmented involving the upper notch and 2% the thyroid membrane. Discussion: In the diagnosis of laryngeal trauma, acute injuries and chronic injuries should be sought, since the functions of the larynx as an anatomical structure and with the function of being the critical intersection for breathing, swallowing and expression, where neuropathies that affect the movement of the vocal cords can significantly affect quality of life. Conclusion: it is essential to have an infrastructure for effective or correct diagnosis and treatment. The trauma surgeon must make decisions regarding the approach, procedure and follow-up, which with his experience and knowledge may be an option to resolve as assertively as possible for the benefit of the patient. Tracheostomy is not currently a strict or forceful indication.